Practice Effects in Mild Cognitive Impairment Increase Reversion Rates and Delay Detection of New Impairments - Sanderson-Cimino, Mark; Elman, Jeremy A.; Tu, Xin M.; Gross, Alden L.; Panizzon, Matthew S.; Gustavson, Daniel E.; Bondi, Mark W.; Edmonds, Emily C.; Eppig, Joel S.; Franz, Carol E.; Jak, Amy J.; Lyons, Michael J.; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: Cognitive practice effects (PEs) can delay detection of progression from cognitively unimpaired to mild cognitive impairment (MCI). They also reduce diagnostic accuracy as suggested by biomarker positivity data. Even among those who decline, PEs can mask steeper declines by inflating cognitive scores. Within MCI samples, PEs may increase reversion rates and thus impede detection of further impairment. Within an MCI sample at baseline, we evaluated how PEs impact prevalence, reversion rates, and dementia progression after 1 year. Methods: We examined 329 baseline Alzheimer’s Disease Neuroimaging Initiative MCI participants (mean age=73.1; SD=7.4). We identified test-naïve participants who were demographically matched to returnees at their 1-year follow-up. Since the only major difference between groups was that one completed testing once and the other twice, comparison of scores in each group yielded PEs. PEs were subtracted from each test to yield PE-adjusted scores. Biomarkers included cerebrospinal fluid phosphorylated tau and amyloid beta. Cox proportional models predicted time until first dementia diagnosis using PE-unadjusted and PE-adjusted diagnoses. Results: Accounting for PEs increased MCI prevalence at follow-up by 9.2% (272 vs 249 MCI), and reduced reversion to normal by 28.8% (57 vs 80 reverters). PEs also increased stability of single-domain MCI by 12.0% (164 vs 147). Compared to PE-unadjusted diagnoses, use of PE-adjusted follow-up diagnoses led to a 2-fold increase in hazard ratios for incident dementia. We classified individuals as false reverters if they reverted to cognitively unimpaired status based on PE-unadjusted scores, but remained classified as MCI cases after accounting for PEs. When amyloid and tau positivity were examined together, 72.2% of these false reverters were positive for at least one biomarker.